Risk factors for hepatitis c virus infection among adult patients at a public hospital in Kedah, Malaysia - Mohd Suan, Mohd Azri (2019)
Hepatitis C virus infection has increasingly become a public health concern in both developed and developing countries. The World Health Organization reported that 71 million persons were living with this chronic hepatitis C virus infection worldwide with global incidence rate accounted for 23.7 per 100,000 population. Malaysia is also reported to have nearly 330 000 adults being infected with this virus. In addition to providing treatment, identifying the potential risk factors to prevent the transmission of HCV are essential to control the hepatitis C infection. However, many known risk factors have not been widely explored in Malaysia. Hence, the aim of the study was to identify the risk factors associated with hepatitis C among adult patients in Kedah state, Malaysia. The conduct of this study has been approved by the Medical Research and Ethics Committee of the Ministry of Health of Malaysia. This matched, hospital-based, casecontrol study was conducted at Hospital Sultanah Bahiyah, Alor Setar, in Kedah state. Cases were adults (aged ≥18 years) diagnosed with hepatitis C from January 2015 until December 2018, while controls were age-, gender-, and ethnic-matched and tested negative for hepatitis C virus. The purpose and method of the study were explained to all participants before obtaining their informed consent. A questionnaire on demographic characteristics and previous exposure to listed risk factors were filled up by all study participants. Association of hepatitis C infection with demographic characteristics, occupational profile, medical history, high-risk activities, and traditional practices were assessed using univariable and multiple logistic regression analysis. All data analyses were performed using R statistical software, Version 3.5.2 A total of 255 case-control patient pairs were enrolled in this study. In both groups, majority of the patients were male, aged 50-59 years, and of Malay/Bumiputra ethnicity. Multiple logistic regression analysis indicate that having a history of blood or blood product transfusion before 1992 (adjusted odds ratio [AOR] 6.99, 95% confidence interval [CI]: 3.73, 13.81), injection drug use (AOR 6.60, 95% CI 3.66, 12.43), imprisonment (AOR 4.58, 95% CI 1.62, 16.40), tattooing (AOR 3.73, 95% CI 1.37, 12.00), having more than one sexual partner (AOR 2.06, 95% CI 1.16-3.69), body piercing (AOR 1.71, 95% CI 1.04, 2.80), and having only secondary education (AOR 1.92, 95% CI 1.06, 3.57) were independently associated with hepatitis C. In conclusion, these findings demonstrate that the risk factor for hepatitis C is multifactorial. Screening activities should give greater attention to these high-risk groups to identify undiagnosed HCV-infected individuals. Better access to HCV screening and treatment at prison and drug rehabilitation facilities, improved public awareness on unsafe use of illicit drugs and formulating safety guidelines for tattooing and piercing, were among recommended strategies to control this chronic viral infection in Malaysia.